Veteran Educators or For-Profiteers? Tuition Responses to Changes in the Post 9/11 GI Bill - Matthew Baird; Michael S. Kofoed; Trey Miller; Jennie Wenger (Institute of Labor Economics (IZA), 2020)
In 2010, Congress reauthorized the Post-9/11 GI Bill by changing reimbursement rates from widely-varying by-state maximums to a nationwide limit. This policy created exogenous variation in the changes in reimbursement rates in direction and magnitude for veterans at private universities. We leverage this variation to examine for-profit college responses to changes in reimbursement rates. We detect tuition responses only for for-profit colleges, where we estimate a one percent pass-through rate. This for- profit response is driven by colleges in states that saw decreased benefits, colleges with higher concentrations of veterans, and colleges whose pre-change tuition was above the state maximum but below the since-increased nationwide level; the last group has a pass-through rate of eight percent. This policy also caused declines in non-veteran populations showing a substitution towards veteran students.
Keywords: I23; I28; H52; H56; 330; for-profit colleges; Post 9/11 GI Bill; price discrimination